THE EFFECTIVENESS OF HYPNOTHERAPY DIRECT SUGGESTION IN IMPROVING THE EMOTIONAL REGULATION OF STUDENTS ADDICTED TO SOCIAL MEDIA - Chandra, Chandra; Wijaya, Angelina Fransiska; Harley, Vincent; Mirza, Rina; Putra, Achmad Irvan Dwi (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to test the effectiveness of the Hypnotherapy Direct Suggestion technique in improving the emotional regulation of students who are addicted to social media. This approach was chosen because hypnotherapy allows individuals to receive positive suggestions that can help them better manage their emotions. The research method used was an experiment with the One Group Pretest-Posttest design, where the research subjects consisted of 15 students of the Faculty of Psychology, Universitas Prima Indonesia, who were selected through purposive sampling techniques. The selection of subjects was based on a high level of social media addiction, which was measured through a scale of social media use intensity. The intervention was carried out in a hypnotherapy session with the direct suggestion technique, which aims to instill positive suggestions into the subject’s subconscious mind. Emotion regulation measurements were carried out before and after the intervention using the Emotion Regulation Questionnaire (ERQ) scale, which has been tested for validity and reliability. The results of data analysis using the Wilcoxon Signed-Rank Test showed a significant improvement in emotion regulation after being given therapy (p < 0.05). In addition, observations and interviews with subjects supported these findings, where participants showed positive behavioral changes, such as reduced time spent using social media and increased awareness of its negative impacts. This research provides important implications for psychological interventions in dealing with social media addiction and improving students’ emotional well-being.